Motivasi di Balik Keputusan Mahasiswa Akuntansi Melanjutkan ke PPAK: Pengaruh Lingkungan Masyarakat, Pengetahuan Akuntansi, dan Prospek Karir - Ni Made Rani Asthiti Irwanti; Komang Krishna Yogantara; Sarita Vania Clarissa (SENTRI: Jurnal Riset Ilmiah, 2026)
Accounting Professional Education (PPAk) is a strategic pathway to produce competent professional accountants; however, students’ interest in pursuing this program remains relatively low. Data from the Ikatan Akuntan Indonesia (IAI, 2025) indicate that the number of certified professional accountants in Indonesia is still disproportionate compared to industrial demand, creating a competency gap in the accounting profession. This study aims to analyze the influence of the social environment, accounting knowledge, and career prospects on accounting students’ decisions to pursue PPAk at Triatma Mulya University. This research employs a quantitative approach using primary data collected through questionnaires distributed to 46 active seventh-semester accounting students selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (SEM-PLS) with SmartPLS 4.0. The results show that all independent variables have a positive and significant effect on students’ decisions to pursue PPAk. Accounting knowledge has the strongest influence (β = 0.492; t = 5.183; p < 0.001), followed by social environment (β = 0.347; t = 3.779; p < 0.001), and career prospects (β = 0.274; t = 2.545; p = 0.011). The model explains 50.9% of the variance in students’ decisions to pursue PPAk (R² = 0.509; Adjusted R² = 0.474), which is categorized as moderate explanatory power. These findings indicate that students’ decisions are shaped by both internal factors (knowledge competence) and external factors (social influence and perceived career opportunities), with technical accounting understanding emerging as the most dominant determinant. This study implies that higher education institutions should strengthen profession-oriented curricula, expand professional certification exposure, and develop strategic programs such as scholarship schemes and direct job-placement partnerships after PPAk completion to enhance students’ interest in professional accounting education.